Youth Suicide in Nepal: A Growing Concern - Paudel, Sudip; Atreya, Alok (Journal of Nepal Health Research Council, 2024)
In Nepal, suicidal behaviour among adolescents is a growing concern, and the country has been in the grip of a major mental health disaster for many years. The issue must be addressed immediately, and there must be urgent and concerted action by state institutions, healthcare practitioners, and society. Official statistics show the increased rates of completed suicide, whereas those cases that attempted suicide and survived the event remain unaccounted for. The fortunate suicide victims, who were timely rescued, resuscitated, and survived; in the recent years as witnessed at a tertiary hospital in the western region of Nepal, depict a grim picture of suicidality among youths, particularly among teenagers and young adults. The authors recognize the urgent need to tackle and address the problem of youth suicide in the country.Keywords: Cultural factors; mental health crisis; Nepal; risk-taking behaviour; suicide prevention.